(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Rooftop rainwater collecting as an alternative supply of drinking water is gaining popularity, particularly in poor nations. The existing data on the water quality of rooftop rainwater collecting systems are reviewed in this article. The impact of several variables on the physicochemical and microbiological quality of collected water is addressed. Different contaminants in roof runoff, such as heavy metals and trace organic pollutants, are compared from different regions of the globe. The findings indicate that the quality of water collected from roof catchments often falls short of drinking-water standards. Unless specific precautions are followed during rainwater collection and storage, most studies show that collected water is highly polluted microbiologically by a range of indicator and pathogenic organisms. In certain instances, heavy metals and trace organics may cause difficulties. The study concludes that the cleanliness of rainwater collected from roofs should not be taken for granted, and that the water should be analyzed for microbial contamination in particular. To make the gathered rainwater drinkable, it would need to be treated properly. The study also highlights the need for further research into appropriate design and management methods for roof-collected rainwater sources to avoid contamination.